Bibliometric Insights into Anger and Aggression Research - Neupane, Dasarath; Lourdusamy, Arputhem (NPRC Journal of Multidisciplinary Research, 2024)
Background: Anger and aggression are central constructs in psychology, sociology, and behavioral sciences, affecting mental health and social interactions. Despite extensive research, there is a need to map the trends and focal points of studies in this area, particularly to understand how themes like mental health disorders, developmental psychology, and social dynamics interconnect with aggression. Objective: This study aims to conduct a bibliometric analysis of global research on anger and aggression, identifying key trends, influential authors, leading research areas, and interdisciplinary approaches. The goal is to provide insights into the trajectory and focus of scholarly work in this field. Methods: Using bibliometric techniques, including co-occurrence mapping and citation analysis, data from relevant research articles were extracted and analyzed through VOSviewer. Key terms, authorship networks, and publication patterns were examined to uncover thematic clusters and research trajectories. Findings: The analysis highlights several prominent themes in the literature on anger and aggression, including their links to psychological disorders (e.g., depression, stress), behavioral development in children and adolescents, and the influence of family and social environments. The co-occurrence analysis also points to growing interest in therapeutic interventions, cognitive and neurological underpinnings of aggression, and biological factors, such as brain injury. Authors such as Richard Tremblay, David Farrington, and Manuel Eisner have emerged as influential figures in this research domain. Conclusion: This bibliometric study reveals that research on anger and aggression is characterized by interdisciplinary approaches, integrating psychology, neuroscience, and social sciences. The focus on mental health and therapeutic interventions highlights the practical applications of this research in clinical settings. The increasing interest in the neurological and biological dimensions of aggression also suggests a broadening of the research agenda. Novelty: This study provides a comprehensive overview of the intellectual landscape of anger and aggression research through a bibliometric lens, offering new insights into the evolving trends, collaboration networks, and thematic directions in the field. It is one of the first studies to integrate a co-occurrence analysis with citation data to map both psychological and biological dimensions of aggression research.